Racial Disparities in Surgical Treatment of Obstructive Sleep Apnea. Issue 1 (March 2022) - Cohen, Samuel M.; Howard, Javier J.M.; Jin, Michael C.; Qian, Jason; Capasso, Robson
Objective: Determine risk factors for failure to receive surgical treatment among patients with obstructive sleep apnea. Study Design: Population-based observational longitudinal cohort study. Setting: Population-based database. Methods: Multivariate analysis of 500, 792 individuals with obstructive sleep apnea from Optum's deidentified Clinformatics Data Mart database (2004-2018). Results: Black race, increased age, diabetes, atrial fibrillation, obesity, and congestive heart failure were independently associated with a decreased rate of surgery for obstructive sleep apnea. Asian race, hypertension, arrhythmias other than atrial fibrillation, pulmonary disease, and liver disease were independently associated with an increased rate of surgery for obstructive sleep apnea. Conclusion: Racial disparities in health outcomes related to health care access and in economic resources have an enormous impact on public health and social equity. We found differences in rates of surgery for obstructive sleep apnea based on race. These data are consistent with others demonstrating disparities in medical treatment of sleep apnea with positive pressure and underline a need for a change in awareness and treatment in these populations.